QUANTITATIVE DIMENSION OF SUBJECTS’ POWER IN REPRESENTATIVE BODY: COALITION AND „POWER INDEXES” - Авксентьєв, А.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The research contains the analysis of calculation aspects of forming and functioning coalitions in representative body. We examine nontrivial cases of disparity between coalition subject power and quantitative composition of fractions. For parliamentary fractions in Verkhovna Rada 5-7 convocation, „power indexes” are determined with the use of modern political study instrument.